Analysis of The Role of Parents in Bringing Out Children's Talents Through The Application of The Gnoti Seauton Socrates Philosophy Method (Research Conducted on Parents of PIAUD Students in Cihanjawar Village, Purwakarta) - Enjang (Universitas Panca Sakti Bekasi, 2024)
This research tries to apply the Socratic Gnoti Seauton Theory with a dialectical (dialogue) model as a parenting pattern at the early childhood age level, to determine its effect on increasing understanding of knowledge where this knowledge will lead children to discover awareness of their own 'self' (to